SALIVARICIN MMAYE1 PRODUCTION IS ENHANCED IN A NEW MEDIUM AND ACTS SYNERGISTICALLY WITH PENTOCIN MQ1 (FUDMA JOURNAL OF SCIENCES, 2022)
Resistance to conventional antimicrobials is burgeoning. Consequently, the world health has mandated researchers to develop novel antimicrobial agents as replacement for conventional antimicrobials. Of the potential alternatives, bacteriocins are widely considered lead compounds. Salivaricin mmaye1 and pentocin MQ1 are bacteriocins produced by Lactobacillus salivarius SPW1 and Lactobacillus pentosus CS2 respectively. These bacteriocins have been reported to possess high antimicrobial activity against human pathogens. The overall objective of this study is to optimize production of salivaricin mmaye1 and evaluate its potential synergistic action with pentocin MQ1. Results revealed that Lactobacillus salivarius SPW1 is non-hemolytic and sensitive to most antibiotics screened but resistant to gentamicin, streptomycin and vancomycin. Resistance to these antibiotics is not mediated by plasmids. Genes encoding salivaricin mmaye1 production are not plasmid-borne. A new medium for high biomass accumulation was developed. Salivaricin mmaye1 production is optimum at pH values of 6 and 7. Salivaricin mmaye1 and pentocin MQ1 exhibited synergism against Micrococcus luteus, Listeria monocytogenes and Pseudomonas aeruginosa. These findings provide a glimpse into future therapeutic applications of salivaricin mmaye1.
Keywords: Antibiotic resistance, Bacteriocin, Salivaricin mmaye1, Lactobacillus salivarius, Synergistic action, Pentocin MQ1